WORK DISCIPLINE REVIEWED BASED PUNISHMENTS AND REWARDS (STUDY OF PT. ACTMETAL INDONESIA) - Melia Putri; Enjang Suherman; Flora Patricia Angela (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Delay shows one of the undisciplined attitudes of employees in complying with the rules that have been set. One way to uphold the level of work discipline is to properly apply punishment and reward. The purpose of this study is to analyze and explain the relationship between punishment and reward with employee work discipline. This study uses a descriptive and verification research approach with quantitative data analysis and survey research methods. The number of samples used was 109 with the slovin formula from a population of 150 employees of PT. Actmetal Indonesia. Data analysis used multiple linear regression for the verification test and analysis of the scale range for the descriptive test. The results of the statistical the scale range for the descriptive test, the results of the statistical analysis show that the correlation coefficient R2 0,835 which indicates that the relationship between the punishment variable (X1) and the reward variable (X2) together with work discipline (Y) has a strong and positive relationship. Keywords: Punishment, Rewards, Work discipline